Effects of mentor–mentee discordance on Latinx undergraduates' intent to pursue graduate school and research productivity. Issue 1 (22nd April 2021) - Morales, Danielle X.; Grineski, Sara E.; Collins, Timothy W.
Abstract: Owing to an undergraduate demographic transition in STEM, Latinx students are likely to work with faculty from different backgrounds when participating in undergraduate research experiences (UREs). However, the effects of mentor–mentee demographic discordance on student STEM development are unclear. This paper examines how mentoring discordance affects Latinx students' intentions to pursue graduate school and research productivity. We collected data from participants in a multiyear, multi‐institutional URE program ( n =  171 dyads), which we analyzed using multivariable generalized estimating equations. Results indicate that compared with gender concordance, gender discordance was associated with a 17% increase in intent to pursue graduate school for Latina students. Compared with racial/ethnic concordance, racial/ethnic discordance was associated with a 38% increase in intent to pursue graduate school for Latino students. When paired with gender discordant mentors, Latina students were 70% less likely to present their URE projects at a professional conference. When faculty mentors were culturally competent and interacted with mentees frequently, Latinx students became more interested in pursuing graduate school. Because mentors from different demographic backgrounds contribute to the development of Latinx STEM students in varied ways, URE program directors should integrate opportunities for multiple mentorships. Abstract : Owing to an undergraduate demographic transition in STEM, Latinx students are likely to work with faculty from different backgrounds when participating in undergraduate research experiences. However, the effects of mentor–mentee demographic discordance on student STEM development are unclear. This paper examines how mentoring discordance affects Latinx students' intentions to pursue graduate school and research productivity.